Process and Impact of Combustion on Cement Oxide Minerals: An Experimental Study - Al-Naffakh, Jameel; Jafar, Israa (International Journal of Environment, Engineering and Education, 2020)
The main stages of the primary materials are that feed the furnaces to form the mineral compounds of cement, which are the stage of drying the materials from water at a temperature of 100 degree Celsius and moving to the crystallization area at a temperature of 550 degree Celsius. Thus, the free lime begins to break down the calcium carbonate by interacting with silica and clay compounds to form (C2S) at a temperature 900 degree Celsius. In the transition region at a temperature of 1260 degree Celsius begins the formation of liquid compounds (C3A, C4AF), where the formation of a compound (C2S) continues and begins to form a compound (C3S). When the temperature rises at 1450 degree Celsius, the formation of the vehicles is complete, and this depends on the quality of the blended raw materials that affect the life of the firing blocks and the fuel consumption. As for the silica coefficient, it has a major role in determining the clinker quality, as the best silica coefficient (2.7) was obtained, as well as the best coefficient of alumina (1.38), as well as obtaining the best lime saturation coefficient (0.96) and the percentage of magnesium oxide not exceeding 5 percent, thus stabilizing the ratio Magnesium oxide to form the best burning plants (108). The difference in the concentration of substances leads to an incomplete chemical reaction and this affects the size of the resulting crystals.